Lars van Trier's The Element of Crime - Holten, Bo 1948- (The Criterion Collection, 2000)
The story of an exiled ex-cop who returns to his old beat to catch a serial killer preying on young girls. Set in Germany, the film is shot in sepia tones with brilliant blue flashes.
New widescreen digital transfer, enhanced für 16x9 television, presented in its orig. aspect ratio of 1.85:1
Orig.: Dänemark 1984
Keywords: Serial murder investigation -- Germany -- Drama; Serial murderers -- Germany -- Drama; Deutschland; Detective and mystery films; Feature films; Video recordings for the hearing impaired